DETERMINAN FAKTOR KEJADIAN CA MAMMAE PADA REMAJA-DEWASA AWAL DI RSUD KOTA BOGOR - Rahayu, Safitri; Pratiwi, Rita Dwi; Sarah, Fitri; Fadhilah, Humaira (Edu Masda Journal, 2024)
ABSTRACTCa Mammae is the most common cancer in early adult women aged 15 to 39 years, there are 5.6 out of all invasive breast cancers in young women compared to older women (Rebecca H. Johnson, MD, 2021). The Bogor City Health Office recorded the three highest cancer cases in 2023 were breast cancer with 597 cases. The purpose of this study is to determine the determinants of Ca Mammae incidence factors in adolescents-early adults at Bogor City Hospital. Methods This research is a quantitative research and the design of this study uses descriptive analysis with a Cross Sectional approach. The population in this study was all early adolescents-adults suffering from Ca Mammae totaling 30 people with a sample of 30 respondents. The technique used is total sampling. Data analysis uses the Chi-Square Test and multivariate analysis uses the logistics binary test. Based on data analysis with the Chi-Square Test test with a degree of significance p<0.05 (5%). The results of the study showed that the results of statistical tests showed a relationship between menarche age and the incidence of Ca Mammae (p-value=0.037). There was a family history relationship with the incidence of Ca Mammae (p-value=0.011). There was a relationship between stress and the incidence of Ca Mammae (p-value=0.042). There was no association between obesity and the incidence of Ca Mammae (p-value=0.261). there was a relationship between consuming ready-to-eat food and the incidence of Ca Mammae (p-value=0.033). Conclusion The variable of consuming ready-to-eat food is the most related factor to the incidence of Ca Mammae in adolescents-early adults at Bogor City Hospital because it has (p-value=0.018). Suggestions for Educational Institutions It is hoped that the results of this study can be used as material and source for the STIKes Widya Dharma Husada Tangerang library on the Determinants of Ca Mammae Incidence Factors in Early Adolescents-Adults.                                                     ABSTRAKCa Mammae merupakan kanker yang paling umum terjadi pada wanita dewasa awal berusia 15 hingga 39 tahun, terdapat 5,6 dari seluruh kanker payudara invasive pada wanita muda dibandingkan dengan wanita lebih tua (Rebecca H.Johnson, MD, 2021). Dinas Kesehatan Kota Bogor mencatat tiga kasus kanker tertinggi tahun 2023 adalah kanker payudara sebanyak 597 kasus. Tujuan Penelitian ini adalah untuk mengetehui determinan faktor kejadian Ca Mammae pada remaja-dewasa awal di RSUD Kota Bogor. Metode Penelitian ini merupakan penelitian kuantitatif dan desain penelitian ini menggunakan deskriptif analtik dengan pendekatan Cross Sectional. Populasi dalam penelitian ini adalah seluruh remaja-dewasa awal yang menderita Ca Mammae berjumlah 30 orang dengan jumlah sampel 30 responden. Teknik yang digunakan adalah total sampling. Analisis data menggunakan Uji Chi-Square dan analisis multivariat menggunakan uji binary logistik. Berdasarkan analisis data dengan uji Uji Chi-Square dengan derajat kemaknaan p<0,05 (5%). Hasil penelitian menunjukan hasil uji statistik ada hubungan usia menarche dengan kejadian Ca Mammae (p-value=0,037). Ada hubungan riwayat keluarga dengan kejadian Ca Mammae (p-value=0,011). Ada hubungan stress dengan kejadian Ca Mammae (p-value=0,042). Tidak ada hubungan obesitas dengan kejadian Ca Mammae (p-value=0,261). ada hubungan antara mengkonsumsi makanan siap saji dengan kejadian Ca Mammae (p-value=0,033). Kesimpulan variabel mengkonsumsi makanan siap saji merupakan faktor yang paling berhubungan dengan kejadian Ca Mammae pada remaja-dewasa awal di RSUD Kota Bogor karena memiliki (p-value=0,018). Saran bagi institusi Pendidikan Diharapkan hasil penelitian ini dapat menjadi bahan dan sumber bagi perpustakaan STIKes Widya Dharma Husada Tangerang tentang Determinan Faktor Kejadian Ca Mammae pada Remaja-Dewasa Awal.